The influence of carbon materials on the absorption performance of polymer-derived SiCN ceramics in X-band. Issue 13 (September 2018) - Feng, Yurun; Guo, Xue; Gong, Hongyu; Zhang, Yujun; Liu, Yu; Lin, Xiao; Mao, Junjie
Abstract: Carbon-containing polymer-derived SiCN ceramics (PDCs-SiCN-C) were successfully fabricated with multi-layer graphene (MLG) and multiwalled carbon nanotubes (MWCNTs) as additives at 1100 °C. The effects of MLG and MWCNTs on the microwave absorption properties of PDCs-SiCN-C ceramics were analyzed. The imaginary permittivity and loss tangent of SiCN-MLG and SiCN-MWCNTs were about 3.4, 0.67 at 11.2 GHz and 3.1, 0.57 at 10.6 GHz, respectively. The minimum reflection loss of SiCN-MLG and SiCN-MWCNTs at 3 mm was − 54 dB and − 48 dB with the effective absorption bandwidth (RL ≤ −10 dB, >90% absorption) about 1.5 GHz and 0.9 GHz in X-band.